Capillary electrophoresis in multidimensional separation techniques for analysis of natural compounds in complex matrices (a review) - Česla, Petr; Dinisová, Petra; Fischer, Jan (Univerzita Pardubice, 2011)
In past decades, capillary electromigration separation methods, based on the differences of migration velocities in high intensity electric field, have been established as the routine analytical techniques suitable for the analyzes of both ionized and non-ionized compounds. The improvement in sensitivity of detection lead to discoveries of new substances presented at trace levels in biological, environmental and food samples. For determination of such compounds, separation methods with high resolving power are needed, which leads to the rapid development of multidimensional separation methods. The article presented here reviews some experimental aspects and applications of capillary electrophoresis in the multidimensional separation systems, focused mainly to its combinations with liquid chromatography. Capillary electrophoresis is being applied in multidimensional systems either in both or presumably in the second dimension due to the speed of the analysis and injected volumes of samples. Advantages and drawbacks of the off-line and on-line experimental setups are discussed. Applications of two-dimensional liquid chromatography-capillary electrophoresis for the separation of naturally occurring compounds are discussed with special emphasis on the possibilities of improvement of the detection sensitivity using in-capillary preconcentration techniques.
Keywords: capillary electrophoresis; micellar electrokinetic capillary chromatography; two-dimensional separations; orthogonality; on-line preconcentration; natural compounds; review